Uji Sensori Dan Uji Kadar Kimia Flakes Berbahan Dasar Tepung Porang Dan Tepung Tempe: Uji Sensori dan Analisis Poksimat Flakes Berbahan Dasar Tepung Porang (Amorphophallus Muelleri) dan Tepung Tempe - Tarigan, Novriani; Tarigan, Fifi Nurjannah; Sherlina, Sherlina; Hasibuan, Yolanda Oktaviani; Saragih, Meysalina (Amerta Nutrition, 2024)
Background: Porang is local food that contains glucomannan beneficial for accelerating satiety. Therefore, they are good food for diets. Objectives: To determine the chemical and sensory content of flakes formulated from porang flour and tempe flour. Methods: This study used a Completely Randomized Design, three treatments and three repetition. The sensory test was conducted on 50 students of Medan Health Polytechnic. Proximate test was conducted to measure the levels of carbohydrate, protein, fat, water, ash, crude fiber, and glucomannan. Data were analyzed with Analysis of Variance (ANOVA). Furthermore, Multiple Range Test (DMRT) was conducted at 5% and calcium oxalate. Results: The sensory test results showed that the color of flakes in treatments 1, 2, and 3 was different, and treatment 3 was the most preferred. The flavor was also different between treatments, and treatment 1 was the most preferred. However, the aroma and texture of porang flour and tempeh flakes did not change after processing. The highest levels of water, ash, protein, fat, crude fiber and breakability were in treatment 3, while the highest levels of carbohydrate, glucoman and calcium oxalate were in treatment 1. The higher proportion of porang flour resulted in better or higher glucoman levels, but with increased calcium oxalate levels. Further studies need to be carried out, in order to produce low and consumable calcium oxalate levels that fulfill the health requirements. Conclusions: Porang flour and tempe flour influenced the sensory test and chemical content test.